Derivation and validation of predictors of oral anticoagulant-related adverse events in seniors transitioning from hospital to home. Issue 206 (October 2021) - Benipal, Harsukh; Holbrook, Anne; Paterson, J. Michael; Douketis, James; Foster, Gary; Ma, Jinhui; Thabane, Lehana
Abstract: Introduction: Oral anticoagulant (OAC)-related adverse events are high post-hospitalization. We planned to develop and validate a prediction model for OAC-related harm within 30 days of hospitalization. Methods: We undertook a population-based study of adults aged ≥66 years who were discharged from hospital on an OAC from September 2010 to March 2015 in Ontario, Canada. The primary outcome was a composite of time to first hospitalization or emergency department visit for a hemorrhagic or thromboembolic event, or mortality within 30 days of hospital discharge. Cox proportional hazards regression was used to build the model. Results: We included 120, 721 patients of which 5423 experienced the outcome. Most patients were aged ≥75 years (59.5%) and were female (55.6%). Sixty percent of the cohort had a follow-up visit with a healthcare provider within 7 days of discharge. Patients discharged on a direct acting OAC versus warfarin (apixaban: Hazard Ratio [HR] 0.82, 95% confidence interval [CI] 0.71-0.94; dabigatran: HR 0.73, 95% CI 0.63-0.84; rivaroxaban: HR 0.79, 95% CI 0.71-0.88), were prevalent users of the dispensed OAC versus incident users (HR 0.82, 95% CI 0.69-0.96), had a joint replacement in the past 35 days (HR 0.40, 95% CI 0.33-0.50) or major surgery during index hospital stay (HR 0.69, 95% CI 0.60-0.80) had a lower risk for the outcome. The Cox model was stable with acceptable discrimination but poor goodness-of-fit. Conclusions: A model for OAC-related harm in the early post-discharge period was developed. External validation studies are required to understand the model's poor calibration. Highlights: Transition from hospital to home is a high-risk period for adverse events. Predictors of OAC-related adverse events early post-discharge are needed. Clinical factors are significant in predicting risk for OAC-related harm. Final cox model was stable with acceptable discrimination but poor goodness-of-fit. Further studies for external validation of our model are required.